Remoção do ácido 2,4-diclorofenoxiacético (2,4-D) por adsorção em carvão ativado pulverizado associado ao tratamento convencional de água para consumo humano - Leal, Waldiléia Pereira (2013)
The 2,4-D is the second most widely used herbicide in Brazil, reaching the public water supply. Due to the limitation of conventional treatment in removing microcontaminants and capacity of activated carbon to remove them, this study investigated the application of powdered activated carbon (PAC) in the removal of 2,4-D in adsorption process associated with conventional treatment using raw water from the Rio Santa Maria da Vitória in equipment jartest. The diagrams of coagulation were constructed through treatability study of water using aluminum sulfate and polyaluminum chloride as coagulants. Tests of adsorption with carbons derived from coconut shells (PAC 1) and pinus (PAC 2) were characterized and evaluated in its ability to remove 2,4-D. The removal of natural organic matter was also determined by measuring the dissolved organic carbon (DOC) and UV absorbance at 254 nm. To detection and quantification of analytes, acids 2,4-D, 2,4,5-T and 2,4-DCP an analytical methodology for high performance liquid chromatography (HPLC/DAD) was developed and validated. Through the adsorption data, the PAC 1 showed greater capacity for removal of 2,4-D and was associated with conventional treatment, fifteen minutes prior, one minute prior to or one minute after the addition of the aluminum sulfate. The results indicated that the addition of coagulant had no effect on adsorption capacity of the PAC 1 which showed to be being effective for the removal of herbicide, given the drinking water quality standards force.